The Impact of User Experience on Purchase Intention in Tik Tok Live Commerce - Destia Restu Ramanda; Muhammad Rizky Mas Alif; Abdul Rohman (Universitas Airlangga, 2026)
TikTok is one of the social media platforms that has the largest user base globally, with an estimated 1 billion users as of October 2022. The purpose of this study is to test whether or not there is an influence of User Experience on Purchase Intention on TikTok Shop through the live streaming feature. This study uses the Theory of Planned Behavior. The paradigm used in this study uses a positivist paradigm with a quantitative research method. Researchers use data collection techniques carried out through questionnaires. And the data collection technique uses a Likert scale. The population used in this study was TikTok Shop Live Streaming users. A sample of 100 respondents was obtained. This sampling was carried out using the Purposive Sampling technique. This study uses the SEM-PLS (Partial Least Squares) method using SmartPLS software version 4.0. We use 7 hypotheses, namely user experience towards perceived value, user emotional towards Perceived Value, Perceived Value towards Purchase Intention, User Experience towards Purchase Intention, User emotional towards Purchase Intention, User experience through perceived value towards purchase intention, and user emotional through perceived value towards purchase intention. The results of this study indicate a positive or significant influence between User Experience and Purchase Intention without mediation. By optimizing user experience and positive emotions during live streaming, TikTok Shop has the potential to increase competitiveness and strengthen its position in the live-commerce-based e-commerce market, where purchasing decisions are not always based on a rational value evaluation process, but can be formed directly through interactive and real-time experiences experienced by users.